Bacterial Subspecies Variation and Nematode Grazing Change P Dynamics in the Wheat Rhizosphere - Irshad, Usman; Yergeau, Etienne (Frontiers in Microbiology, 2018)
Low phosphorus soils are thought to constitute the majority of soils worldwide and cannot support intensive agriculture without high fertilizer inputs. Rhizospheric Rhizobacteria are well-known to modify P dynamics, and an increased bacterial diversity normally has a positive impact on process rate. However, it is not well known how variation in bacterial diversity at the subspecies level could influence trophic interactions in the rhizosphere and its consequences on plant P nutrition. We therefore hypothesized that the interactions between closely related P solubilizing bacteria and their grazing nematodes could improve plant P dynamics from an unavailable P source. We isolated four Pseudomonas poae strains and extracted nematodes from a Saskatchewan wheat field soil sample. The potential of all bacterial isolates and with and without nematodes combinations for increasing P availability in the wheat rhizosphere was tested in controlled microcosms with Ca3(PO4)2 as sole P source. Liberated P, phosphatase activity, plant P and bacterial abundance based upon phnX gene copies were determined. Phosphorus solubilization efficiency of isolates varied as P. poae 1 >P. poae 2 > P. poae 3 > P. poae 4, respectively whereas phosphatase enzyme activity was only detected under nematodes grazing and during the first 15 days of the experiment. Nematodes grazing upon individual Pseudomonas poae increased phosphatase enzyme activity, bacterial abundance, but decreased plant P concentration compared to non-grazed system. In contrast, the treatment combining all Pseudomonas poae isolates together with nematodes resulted in significant increases in P availability and plant P concentration. Diverse P-solubilizing efficiency and interaction with nematodes within the same bacterial “species” suggest that P dynamics might be linked to micro variation in soil diversity that would not accurately be picked up using common tools such as 16S rRNA gene sequencing.